CgNrdp1, a conserved negative regulating factor of MyD88-dependent Toll like receptor signaling in oyster Crassostrea gigas. Issue 74 (March 2018) - Sun, Rui; Qiu, Limei; Yi, Qilin; Wang, Mengqiang; Yue, Feng; Wang, Lingling; Song, Linsheng
Abstract: Toll like receptor (TLR) signaling cascades are under precise regulations to ensure the proper immune responses during various pathogen invasions. The neuregulin receptor degradation protein-1 (Nrdp1) has been demonstrated to be a novel negative regulator of TLR signaling by targeting MyD88 to induce degradation in mammals. In the present study, an Nrdp1 homologue, Cg Nrdp1, was identified from the genome of Pacific oyster Crassostrea gigas . It contained an open reading frame encoding a polypeptide of 315 amino acids which shared high identities with other homologues from different species. There was a conserved RING domain in Cg Nrdp1, indicating the functional E3 ubiquitin ligase activity. The bacterially expressed recombinant Cg Nrdp1 and Cg MyD88 showed much stronger affinity compared to control groups in the ELISA assay, showing the interacting ability between Cg Nrdp1 and Cg MyD88. When Cg MyD88 or Hs MyD88 was co-transfected with Cg Nrdp1 into HEK293T cells, the luciferase activities of NF-κB were significantly decreased compared to those in MyD88 single-transfection groups, indicating the conserved negative regulating function of Cg Nrdp1 on the MyD88 induced TLR signaling. These results indicated that Cg Nrdp1 was a negative regulator of TLR signaling in oyster and the Nrdp1-MyD88 axis was functional and highly conserved from mollusks to mammals in the negative regulation of TLR signaling. Highlights: A highly evolutionary conserved Nrdp1 homologous gene was identified from Crassostrea gigas. Cg Nrdp1 could directly bind Cg MyD88 in an assay using recombinant proteins. Cg Nrdp1 negatively controlled MyD88-dependent TLR signaling upon over-expression of CgMyD88. CgNrdp1 also negatively regulated HsMyD88 dependent TLR signaling in HEK 293T cells.